Efikasi diri dan pengambilan keputusan karir pada mahasiswa tingkat akhir - Putri, Anggun Fadillah; Priyanggasari, Al Thuba Septa; Taufiqurrahman, Taufiqurrahman (UIN Maulana Malik Ibrahim Malang, 2024)
ABSTRACTThe Central Statistics Agency at Malang in 2022 noted that 14% of the 360,000 unemployed were college graduates. Doubts about career choices are considered to be able to contribute to high unemployment rates. Students who are in the early adult development phase are required to be able and realistic in choosing a career. This research aims to determine the relationship between self-efficacy and career decision-making among final-year students in Malang City. The respondents used in this research were 100 people using a purposive sampling technique. The results of the correlation test show that there is an influence of self-efficacy on career decision-making (R = 0.904 and R squared = 0.817). This shows that self-efficacy is able to have an influence of 81.7% on final-year student career decision-making. The implication of this research is that students are expected to be able to further increase their self-efficacy to improve career decisions in the future.KEY WORDS: Self-efficacy; career decision making; college student ABSTRAKBadan Pusat Statistik Kota Malang tahun 2022 mencatat bahwa 14% dari 360.000 pengangguran adalah berasal dari lulusan perguruan tinggi. Keraguan akan pemilihan karir dianggap mampu menyumbang tingginya angka pengangguran. Mahasiswa yang termasuk ke dalam fase perkembangan dewasa awal, dituntut mampu dan realistik dalam menentukan karir. Penelitian ini bertujuan untuk mengetahui adanya keterkaitan antara efikasi diri terhadap pengambilan keputusan karir pada mahasiswa akhir di Kota Malang. Responden yang digunakan dalam penelitian ini adalah 100 orang dengan teknik pengambilan sampel purposive sampling. Hasil uji korelasi menunjukkan adanya pengaruh dari efikasi diri terhadap pengambilan keputusan karir sebesar R = 0,904 dan R Square = 0,817. Hal ini menunjukan efikasi diri mampu memberikan pengaruh sebesar 81,7% terhadap pengambilan keputusan karir mahasiswa akhir. Implikasi dari penelitian ini adalah mahasiswa diharapkan mampu semakin meningkatkan efikasi diri untuk meningkatkan keputusan karir di masa mendatang.KATA KUNCIEfikasi diri; pengambilan keputusan karir; mahasiswa tingkat akhir Copyright ©2024. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. link: CreativeCommons — Attribution-NonCommercial-ShareAlike 4.0 International — CCBY-NC-SA 4.0